Теоретичні основи технологій гетерогенно-каталітичного одержання акрилатних мономерів - Івасів, Володимир Васильович (Національний університет "Львівська політехніка", 2021)
Дисертація присвячена розробленню наукових основ та технології гетерогеннокаталітичного одержання акрилатних мономерів. Розроблено нові ефективні каталізатори виробництва метилметакрилату та метакрилової кислоти за реакціями конденсації пропіонової кислоти з формальдегідом, конденсації метилпропіонату з формальдегідом, та суміщеної конденсації метилпропіонату і пропіонової кислоти з формальдегідом та естерифікації метанолом. Розроблені каталізатори також є ефективними у процесах виробництва метилакрилату та акрилової кислоти. Встановлено залежності між якісним і кількісним складом розроблених каталізаторів та їх фізико-хімічними і каталітичними властивостями. Встановлено вплив технологічних параметрів на процеси синтезу метилметакрилату та метакрилової кислоти. Розроблено кінетичні моделі реакцій газофазної конденсації пропіонової кислоти та метилпропіонату з формальдегідом, їх основі яких виконано оптимізацію процесів та розроблено технологічні схеми виробництва акрилатних мономерів конденсацією карбонільних сполук в газовій фазі. Виконано порівняльний аналіз розроблених каталізаторів та технологій виробництва акрилатних мономерів з існуючими в промисловості, та здійснено дослідно-промислову апробацію. Диссертация посвящена разработке научных основ и технологии гетерогеннокаталитического получения акрилатных мономеров. Разработаны новые эффективные катализаторы производства метилметакрилата и метакриловой кислоты за реакциями конденсации пропионовой кислоты с формальдегидом, конденсации метилпропионата с формальдегидом, и совмещенной конденсации метилпропионата и пропионовой кислоты с формальдегидом и этерификации метанолом. Разработанные катализаторы также эффективны в процессах производства метилакрилата и акриловой кислоты. Установлены зависимости между качественным и количественным составом разработанных катализаторов и их физико-химическими и каталитическими свойствами. Установлено влияние технологических параметров на процессы синтеза метилметакрилата и метакриловой кислоты. Разработаны кинетические модели реакций газофазной конденсации пропионовой кислоты и метилпропионата с формальдегидом, на основе которых выполнено оптимизацию процессов и разработаны технологические схемы производства акрилатных мономеров конденсацией карбонильных соединений в газовой фазе. Выполнен сравнительный анализ разработанных катализаторов и технологий производства акрилатных мономеров с существующими в промышленности, и осуществлено опытно-промышленную апробацию. The dissertation is devoted to the development of scientific foundations and technologies of heterogeneous catalytic production of acrylate monomers. New efficient catalysts are developed for methyl methacrylate and methacrylic acid production by reactions of condensation of propionic acid with formaldehyde, condensation of methyl propionate with formaldehyde, and combined condensation of methyl propionate and propionic acid with formaldehyde and esterification with methanol. The effect of technological parameters on the processes of synthesis of methyl methacrylate and methacrylic acid is established. It is determined that B–P–Zr–W–Ox/SiO2 catalyst with an atomic ratio of components B:P:Zr:W = 3:1:0,15:0,15 is the most efficient by the yield and selectivity of methyl methacrylate and methacrylic acid. Under the optimal conditions of the process at a temperature of 623 K and the residence time of 12 second, the total yield of methyl methacrylate and methacrylic acid is 46.7% per pass, and 93.3%, taking into account recirculation. The correlation between the activity of catalysts and the acidity of their surface was established and confirmed, as well as a reverse correlation between acrylate selectivity and the strength of acidic active sites. It is shown that the processes of condensation of methylpropionate, propionic acid and formaldehyde are most efficiently occurring in the pores of a radius of 3.6 - 6 nm on relatively weak acidic active sites with the activation energy of ammonia desorption less than 30 kJ/mol. The kinetic models of gas-phase methyl methacrylate and methacrylic acid production by condensation reactions are developed, and based on them the process optimization is performed and technological schemes are developed for the heterogeneous catalytic production of acrylate monomers. A comparative analysis of the developed catalysts and technologies for the production of acrylate monomers with existing in industry has been performed, and experimental and industrial testing was carried out. Industrial implementation of developed methods will eliminate the low-selective step of oxidation of acrolein to methacrylic acid, reduce the total number of stages, increase the selectivity of the target products by ~ 20% and reduce the cost of raw materials by 10-18%.
Теоретические основы технологий гетерогеннокаталитического получения акрилатных мономеров
Theoretical basis of technologies of heterogeneous catalytic production of acrylate monomers
Keywords: гетерогенний каталіз; оксидні каталізатори; конденсація; естерифікація; акрилатні мономери; метакрилова кислота; метилметакрилат; гетерогенный катализ; оксидные катализаторы; конденсация; этерификация; акрилатные мономеры; метакриловая кислота; метилметакрилат; heterogeneous catalysis; oxide catalysts; condensation; esterification; acrylate monomers; methacrylic acid; methyl methacrylate; 541.128.13: 66.095.3:661.742.24